Light Induced Inhibition of Protein Phosphatase Calcineurin. Issue 10 (15th September 2014) - Quintero, Andres; Lin, Weilin; Hermann, Sophia; Zhang, Yixin
Abstract Light‐induced switching of drug activity can be used to realize spatio‐temporal control of biological activity in cells and in vivo. In our study of light‐switchable derivatives of immunosuppressive drug cyclosporin A (CsA) in their inhibition of protein phosphatase calcineurin (CaN), we have discovered that 7‐methyl‐6‐thioguanosine (MESG) inhibits CaN under light irradiation through a photo‐crosslinking mechanism. The inhibition has shown selectivity over other enzymes such as phosphatase PP2A, protease chymotrypsin, and cyclophilin 18, the receptor protein for CsA. The discovery could pave the way to discover new covalent inhibitors for protein phosphtase, to design immunophilin‐independent CaN inhibitors, and to design new light controlled inhibitors to modulate signal transduction.